2022
DOI: 10.1007/jhep08(2022)305
|View full text |Cite
|
Sign up to set email alerts
|

Phases of rotating baryonic matter: non-Abelian chiral soliton lattices, antiferro-isospin chains, and ferri/ferromagnetic magnetization

Abstract: A chiral soliton lattice (CSL), proposed as the ground state of rotating baryonic matter at a finite density, is shown to be unstable in a large parameter region for two flavors owing to pion condensations, leading to two types of non-Abelian (NA) CSL phases (dimer and deconfining phases). We determine the phase diagram where the dimer phase meets the other phases and QCD vacuum at three tricritical points. The critical angular velocity of NA-CSLs is lower than that of η-CSL. Each NA soliton carries an isospin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…Finally, note that the original prediction of the CSL phase in QCD under strong magnetic fields [1] was subsequently extended to related setups where either the external conditions or the dynamical theory itself may differ. This applies in particular to dense QCD matter under uniform rotation in presence of a baryon or isospin chemical potential or both [34][35][36], QCD in external magnetic field and with nonzero isospin chemical potential [37,38], and a class of QCD-like theories with nonzero magnetic field and baryon chemical potential [39,40]. We expect the computational techniques developed here to be useful also in these other contexts, should one be interested in the effects of quantum or thermal fluctuations therein.…”
Section: Summary and Discussionmentioning
confidence: 93%
“…Finally, note that the original prediction of the CSL phase in QCD under strong magnetic fields [1] was subsequently extended to related setups where either the external conditions or the dynamical theory itself may differ. This applies in particular to dense QCD matter under uniform rotation in presence of a baryon or isospin chemical potential or both [34][35][36], QCD in external magnetic field and with nonzero isospin chemical potential [37,38], and a class of QCD-like theories with nonzero magnetic field and baryon chemical potential [39,40]. We expect the computational techniques developed here to be useful also in these other contexts, should one be interested in the effects of quantum or thermal fluctuations therein.…”
Section: Summary and Discussionmentioning
confidence: 93%
“…In the case of ϵ < 0 denoted by the blue shaded region in figure 2, the CSL is the Abelian confined CSL. The critical angular velocity in the Abelian CSL is known to be S = 4/π [12,53]. In the case of ϵ = 0 denoted by the green line in figure 2, the up and down solitons do not interact, and they form lattices independently.…”
Section: Jhep03(2024)019mentioning
confidence: 99%
“…moduli as a consequence of the spontaneous breaking of the vector symmetry SU(2) V in the vicinity of each soliton [53]. In such a non-Abelian CSL, we have shown that the effective world-volume theory of a single non-Abelian soliton is a d = 2 + 1 dimensional CP 1 model [O(3) model] with a topological term originated from the WZW term, eq.…”
Section: Jhep03(2024)019mentioning
confidence: 99%
See 2 more Smart Citations